Clinical characteristics and risk factors analysis of 505 cases of infusion reactions in a tertiary hospital - Yin, Weiwei; Wen, Bingqin; Wang, Guoan; Wang, Zhipeng; Kong, Xuetao; Wu, Yaozhou; Meng, Xiao; Ou, Xinyi; Wei, Li; Yu, Pengjiu (Frontiers in Pharmacology, 2024)
The clinical characteristics and risk factors of infusion reactions (IRs) are inadequately described in clinical practice due to underreported cases. In the present study, we reported the current status of IRs based on an in-hospital pharmacovigilance database of a tertiary care hospital. Methods: Our study conducted a retrospective analysis of drug-induced IRs recorded at an inhospital pharmacovigilance center between January 2015 to December 2019. The descriptive statistical analysis encompassed main causative agents, clinical manifestations, organ/system involvement and outcome. The severity of IRs was assessed with reference to the CTCAE version 5.0 criteria and we investigated risk factors associated with severe IRs. Results: During the study period, a total of 505 cases of inpatient drug-induced IRs were detected, of which 79.2% (400 cases) were classified as general IRs and 20.8% (105 cases) were categorized as severe IRs. The primary drugs responsible for these reactions were antibiotics (23%, 116 cases), with piperacillin sodiumsulbactam sodium being the most prevalent, followed by antineoplastic agents (18.4%, 93 cases) and traditional Chinese medicine injections (TCMIs) (12.9%, 65 cases). The administration of cefoperazone -sulbactam, mannatide, Shenqi Fuzheng, elemene, and diterpene ginkgolides meglumine resulted in a higher incidence of critical IRs. Among all cases of IRs, 43.2%, 41.2%, and 23.4% showed signs and symptoms of circulation, skin mucosa, and respiratory organs/systems, respectively. 9.1% of cases experienced systemic damage, while 7.1% and 5.9% of cases reported neurological and gastrointestinal related adverse reactions, respectively. The multivariate analysis revealed that alcohol consumption (OR=2.389, 95% CI 1.141-5.002, P=0.021), age over 65 (OR=1.814, 95% CI 1.052-3.127, P=0.032) and the utilization of contrast media (OR=4.072, 95% CI 1.903-8.713, P<0.001) were identified as risk factors for the development of severe IRs. Conclusions: Understanding the clinical characteristics of IRs helps to implement effective pharmaceutical monitoring and appropriate preventive measures for susceptible populations with risk factors.